Electric circuits - Nilsson, James William; Riedel, Susan A (Boston : Prentice Hall, 2011)
Designed for use in a one or two-semester Introductory Circuit Analysis or Circuit Theory Course taught in Electrical or Computer Engineering Departments. "Electric Circuits 9/e" is the most widely used introductory circuits textbook of the past 25 years. As this book has evolved over the years to meet the changing learning styles of students, importantly, the underlying teaching approaches and philosophies remain unchanged. The goals are: - To build an understanding of concepts and ideas explicitly in terms of previous learning - To emphasize the relationship between conceptual understanding and problem solving approaches - To provide students with a strong foundation of engineering practices
Includes bibliographical references and index
Keywords: Electric circuits